Sodium periodate/TEMPO as a selective and efficient system for amine oxidation. Issue 18 (7th March 2018) - Galletti, P.; Martelli, G.; Prandini, G.; Colucci, C.; Giacomini, D.
Abstract : NaIO4 /TEMPO efficiently allowed a metal-free oxidation of benzylamines to benzaldehydes with complete selectivity for N -benzyl residues in secondary amines. Abstract : A new metal-free protocol for promoting oxidation of amines in aqueous-organic medium was developed. NaIO4 and TEMPO as the catalyst emerged as the most efficient and selective system for oxidation of differently substituted benzyl amines to the corresponding benzaldehydes without overoxidation. Unsymmetrical secondary amines underwent selective oxidation only at the benzylic position thus realising an oxidative deprotection of a benzylic group with an easy amine recovery.